Japan’s Assistance for Sustainable Peace and Development in the Bangsamoro Post-Conflict Reconstruction - Nur Azizah; Alya Khasuna Umar (ARISTO, 2026)
The Since 2002, Japan has contributed approximately 26 billion pesos for the sustainable peace and development efforts in Mindanao through Official Development Assistance (ODA), which aligns with the objectives of the Sustainable Development Goals (SDGs). Following the peace agreement between the Philippine government and the Moro separatist group, Japan provided an additional USD 13 million for post-conflict reconstruction. This article examines the rationale behind Japan’s foreign aid in the post-conflict reconstruction of Bangsamoro. Employing a qualitative research methodology with a descriptive-analytical approach, this study draws on secondary data from reputable academic journals indexed in Scopus and Sinta, as well as official reports from the Japanese Ministry of Foreign Affairs, the Bangsamoro government, and credible news sources. Primary data was obtained through observation and interviews with stakeholders in Bangsamoro during the author’s internship at the Al Qalam Institute, Ateneo de Davao University, a non-governmental organization committed to interfaith harmony and community empowerment for peace and sustainable development. The analysis applies a realist perspective using Hans Morgenthau’s A Political Theory of Foreign Aid as the theoretical framework. The findings suggest that while Japan’s ODA significantly contributes to regional development and stability in Bangsamoro, it simultaneously advances Japan’s geopolitical and economic interests, particularly in countering China’s assertiveness in the South China Sea and its economic dominance in Southeast Asia. Keywords : Japan; Official Development Assistance (ODA); Sustainable Development and Peace; Bangsamoro; Post-Conflict Reconstruction;